Documentation, Documentary, and the Law: What Should Be Made of Victim Impact Videos? - Austin, Regina (2010)
Since the Supreme Court sanctioned the introduction of victim impact evidence in the sentencing phase of capital cases in Payne v. Tennessee, 501 U.S. 808 (1991), there have been a number of reported decisions in which that evidence has taken the form of videos composed of home-produced still photographs and moving images of the victim. Most of these videos were first shown at funerals or memorial services and contain music appropriate for such occasions. This article considers the probative value of victim impact videos and responds to the call of Justice John Paul Stevens, made in a statement regarding the rejection of certiorari in People v. Kelly, 129 S.Ct. 564 (2008), for the articulation of reasonable limits on the admission of victim impact evidence. The first part of the article offers an analysis of victim impact videos drawing on the lessons of cinema studies and cultural studies. The common reception of home photographs and moving images affects the interpretation of victim impact videos. As a result, impact videos are typically too idealistic and idyllic to be really probative evidence of the victims’ individuality and the impact of their loss on their families and friends. However, impact videos may be particularly important evidence for the members of devalued or denigrated groups who fall outside of generally accepted images of ideal victims. The second part of the article deals with an actual case in which the subject of the video was a young Latina mother, felled by domestic violence, whose character was attacked as part of the effort to mitigate her husband’s sentence. He wound up with a judgment of life without the possibility of parole. Here the article considers how the victim impact video might have been more probative and the response of the defense to it, more likely to produce a less harsh punishment. Part three finds greater relevance in a video streamed on YouTube that was based on the written impact statement presented by the young adult son of a homicide victim at the perpetrator’s first parole hearing which was held some 15 years after the murder. Finally, the conclusion offers recommendations for the admission of victim impact videos